Application of Markov Chain in Predicting Sugar Production at Candi Baru Sugar Factory, Sidoarjo - Agustina Pradjaningsih; Ardelia Nani Vidatiyasa; Kiswara Agung Santoso (Pattimura Proceeding, 2023)
Granulated sugar is a sugar commonly used daily to manufacture food and beverages. The demand for granulated sugar continues to increase, but the number of sugar factories and the area of ​​sugar cane in Indonesia is decreasing. This causes a gap between the demand for sugar which continues to increase, and the production of granulated sugar continues to decline, resulting in Indonesia being the largest country importer of sugar. The imbalance between the demand and production of granulated sugar At Candi Baru Sugar Factory, Sidoarjo, East Java, resulted in not achieving the target to meet these needs. Therefore, predictions are made to get an overview of production planning to optimize granulated sugar production so that sugar needs can be met. The prediction method used at the Candi Baru sugar factory, Sidoarjo, East Java, for the 2022 milling period is the Markov Chain method with a four-state divisor, namely drastically down, down, up, and up drastically. The application of Markov Chains produces predictions for each state. It is predicted that the production of sugar with the highest percentage for May – December upstate.